Mobilization pathways of organic carbon from permafrost to arctic rivers in a changing climate - Guo, L. D.; Ping, C. L.; Macdonald, R. W. (Geophysical Research Letters, 2007)
[1] Arctic warming may cause the release of vast amounts of soil organic carbon (SOC) from permafrost, which will manifest itself in the fluxes and composition of organic carbon in northern rivers and Arctic coastal regions. To elucidate the transport pathways of SOC, radiocarbon composition was measured for dissolved organic carbon (DOC), particulate organic carbon (POC), sediments and SOC from the Mackenzie, Sagavanirktok, and Yukon river basins, and soil leaching experiments were conducted. The radiocarbon ages of riverine suspended POC and sediments ranged from 4430 to similar to 7970 yr BP, while DOC was much younger (390-1440 yr BP) except samples from the Sag River. Soil leaching experiments released
id: 773; 187WS Times Cited:23 Cited References Count:29Y